Use of the Adaptive Behaviour Dementia Questionnaire in a Down Syndrome Specialty Clinic - Nicolas M. Oreskovic; Ayesha Harisinghani; Caroline Bregman; Clorinda Cottrell; Margaret Pulsifer; Brian G. Skotko; Amy Torres; Alexa Gozdiff Spognardi; Stephanie L. Santoro (Journal of Integrative Neuroscience)
Objective: To study the use of a dementia screening tool in our clinic cohort of adults with Down syndrome. Study Design: A retrospective chart review of patients with Down syndrome was conducted to follow the use of the Adaptive Behaviour Dementia Questionnaire (ABDQ) in a dementia screening protocol. The ABDQ results for patients aged 40 years and older at a Down syndrome specialty clinic program were assessed. Based on caregiver feedback, an ABDQ with modified instructions was piloted and the impact assessed. Results: As part of our clinic’s initiative to implement a new clinical protocol to screen for dementia, the ABDQ was completed by 47 caregivers of adults with Down syndrome, aged 39 years and above, from December, 2021 to April, 2023. Based on clinical impressions at the same timepoint, the ABDQ had a sensitivity of 0%, specificity of 97.4%, positive predictive value of 0%, and negative predictive value of 80.4%. Nine patients were deemed to have mild cognitive impairment and/or dementia by clinical impressions, but they did not identify as positive on the ABDQ. The Down syndrome clinic team modified the ABDQ in an effort to provide clearer language and increased sensitivity. The modified ABDQ showed a sensitivity of 0%, specificity of 93.8%, positive predictive value of 0% and negative predictive value of 75%. Conclusion: Neither the original ABDQ nor a modified version adequately identified patients with cognitive impairment and/or dementia within the Down syndrome clinical program. The inability to replicate findings from the initial ABDQ validation may be due to differences in setting and format.